Workflow for the isolation of natural product secondary metabolites using off-line SPE guided by gradient reverse-phase liquid chromatography (LCSPE-fast) - Pavão, Lyamara M. O.; Barbosa, Marília F.; Pereira, Ana Maria S.; Cass, Quezia B.; Lopes, Adriana A. (Frontiers in Natural Products, 2025)
The importance of natural products (NPs) as molecular libraries providing diverse three-dimensional structural features and serving as scaffolds for drug discovery is well recognized. However, the isolation of both targeted and untargeted secondary metabolites remains a major challenge in NP research, despite significant advances in analytical and biotechnological tools. To address this, we report a rapid and efficient method for the semipreparative isolation of secondary metabolites from NP extracts using offline C18 solid-phase extraction (SPE) cartridges, guided by the retention profile of a reverse-phase liquid chromatography gradient (LCSPE-fast). LCSPE-fast proved to be fast, cost-effective, and yielded multi-milligram amounts of target-metabolite-enriched fractions (∼0.40 g of chlorogenic acid and 0.03–0.103 g of 3,4-Di-O-caffeoylquinic acid) from Uncaria guianensis cultivated both in vitro and in situ.